Modification of Teaching/Learning Strategies of University Teaching Staff - O. A. Dyomina; I. A. Tepleneva (Высшее образование в России)
The paper considers the problem of changing the traditional model of higher education into the up-dated model of blended learning. The paper focuses on the problem of changing the teaching/learning strategies as the necessary condition for creating and improving the modified educational environment at Universities taking into consideration the advanced achievements in science and social development. The article dwells on the existing possibilities for a student-centered teaching/learning process where the student creates his individual educational track. The authors have considered the reimagining means of teaching/learning strategies for teaching staff by aiming at effective blended learning. Having analyzed the results of pilot studies, shortcomings of conventional teaching and statistical information on graduate employment, the authors have stated the fact that neither conventional teaching nor the so-called innovative educational technologies could close the gap between educational aims and results. The acute shortage of up-dated theoretical psychological and peda gogical knowledge as well as the lack of due consideration for reimagining of teaching/learning strategies have been suggested as the deep-rooted causes of this gap. The paper suggests the definition of teaching/learning strategies and the developed model of their application for University educational environment. The authors have shown the existed blended learning models and the experience of their implementation in the Russian Federation and abroad. The role of educational moderator at creating a new type of teaching/learning interaction by using a Tutorial FL Navigator has been justified and illustrated by FLT at University. The student turns into a member of academic community while entering the environment of Content and Language Integrated Learning Project (CLILP). The potential prospects of blended learning model have been analyzed using the project method in teaching foreign languages (Content and Language Integrated Learning Project). The conclusion of blended learning effectiveness for transformation the general foreign language teaching into expanded professional education has been drawn on the base of obtained empiric and statistical evidence.